Involving Minors in Medical Decision Making: Understanding Ethical Issues in Assent and Refusal of Care by Minors - Lang, Abigail; Paquette, Erin Talati (Seminars in Neurology, 2018)
When caring for minors, the clinician–patient relationship becomes more ethically complex by the inclusion of parents in the clinician–parent–patient triad. As they age, children become more capable of participating in the decision-making process. This involvement may lead them to either accept or refuse proposed care, both of which are ethically acceptable positions when the minor's capacity to participate in decision making is carefully considered in the context of their age, development, and overall health. Certain conditions may be more likely to impact their capacity for participation, but it is important for clinicians to avoid categorical presumption that minors of a certain age or with certain conditions are incapable of participating in decisions regarding their care. Understanding the ethical bases for decision making in pediatric patients and considerations for the involvement of minors who both assent to and refuse proposed treatment will equip clinicians to respect the growing autonomy of minor patients.
Keywords: assent; informed consent; pediatrics; treatment refusal; capacity